Penerapan Bimbingan Klasikal Untuk Meningkatkan Keterampilan Sosial Siswa Kelas 10 Di SMA Muhammadiyah 2 Genteng Menggunakan Pembelajaran Kooperatif Tipe Jigsaw - Yuliyanti, Siti; Herlina, Anita; Yayuk, Erna (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2025)
This study aims to implement classical guidance in improving the social skills of tenth-grade students at SMA Muhammadiyah 2 Genteng through the cooperative learning method of the jigsaw type. The research employed a Guidance and Counseling Action Research (PTBK) approach conducted in two cycles, consisting of planning, implementation, observation, and reflection stages. The subjects were 33 students of class X.3 who experienced difficulties in interacting with peers and teachers. Data were collected through observation, questionnaires, and documentation. The findings revealed a significant improvement in students’ social skills after the application of classical guidance integrated with the jigsaw method, as indicated by the increase in self-confidence, communication skills, and group collaboration. The novelty of this research lies in the integration of cooperative learning models into classical guidance services, which are generally dominated by lecture methods. The contribution of this study provides an alternative strategy for guidance services that is more interactive, collaborative, and contextual, serving as a practical reference for school counselors to optimize students’ social skill development in secondary education